How are farmers managing climate risks in India? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Fransesco Fiondella, from the International Research Institute for Climate and Society (IRI), has visited four states in India to gather footage on the kinds of tools and technologies available to farmers to help them manage climate and weather risks. The trip was funded by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and IRI. Please credit: F. Fiondella (IRI/CCAFS)